2021
DOI: 10.3389/fchem.2021.690781
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Deposited Polyoxazoline Films Integration Into Spiral Microfluidics for the Targeted Capture of Size Selected Cells

Abstract: Biomolecules readily and irreversibly bind to plasma deposited Polyoxazoline thin films in physiological conditions. The unique reactivity of these thin films toward antibodies is driving the development of immunosensing platforms for applications in cancer diagnostics. However, in order for these coatings to be used as advanced immunosensors, they need to be incorporated into microfluidic devices that are sealed via plasma bonding. In this work, the thickness, chemistry and reactivity of the polyoxazoline fil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…[ 10 ] Furthermore, the ability of these films to selectively capture cells in the high‐shear environment of a microfluidic device is maintained. [ 11 ] More recently, we have reported the use of POx thin films to functionalize electrodes in electrochemical biosensors. [ 12 ] Other groups have also shown that plasma‐polymer films can be used as part of a nanocomposite to functionalize electrodes and develop biosensors with a low limit of detection and good sensitivity and selectivity.…”
Section: Introductionmentioning
confidence: 99%
“…[ 10 ] Furthermore, the ability of these films to selectively capture cells in the high‐shear environment of a microfluidic device is maintained. [ 11 ] More recently, we have reported the use of POx thin films to functionalize electrodes in electrochemical biosensors. [ 12 ] Other groups have also shown that plasma‐polymer films can be used as part of a nanocomposite to functionalize electrodes and develop biosensors with a low limit of detection and good sensitivity and selectivity.…”
Section: Introductionmentioning
confidence: 99%